Androgen receptor modulatory miR-1271-5p can promote hormone sensitive prostate cancer cell growth - Kalofonou, Foteini; Leach, Damien A.; Powell, Sue M.; Waxman, Jonathan; Fletcher, Claire E.; Bevan, Charlotte L. (Frontiers in Oncology, 2024)
Abstract In most patients with advanced prostate cancer treated with hormonal therapy, androgen independence eventually emerges, leading to death. Androgen receptor signalling remains an important prostate cancer driver, even in the advanced disease stage. MicroRNAs (miRs), non-coding RNAs that regulate gene expression by inhibiting translation and/or promoting degradation of target mRNAs, can act as tumour suppressors or “oncomiRs” and modulate tumour growth. Because of their stability in tissues and in circulation, and their specificity, microRNAs have emerged as potential biomarkers, as well as therapeutic targets in cancer. We identified miR-1271-5p as an androgen receptor modulatory microRNA and we show it can promote hormone sensitive prostate cancer cell growth. Inhibition or overexpression of miR-1271-5p levels affects prostate cancer cell growth, apoptosis and expression of both androgen receptor target genes and other genes that are likely direct targets, dependent on androgen receptor status, and tumour stage. We conclude that miR-1271-5p has the potential to drive progression of hormone-dependent disease and that the use of specific inhibitors of miR-1271-5p may have therapeutic potential in prostate cancer.